ANALISA FAKTOR DOMINAN YANG MEMPENGARUHI WANITA PASANGAN USIA SUBUR TERHADAP PENGGUNAAN METODE KONTRASEPSI TUBEKTOMI - GF Gustina Siregar; Tetty Junita Purba (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2018)
Abstrac Tubectomy is a medical procedure in the form of closure of the uterine tube with a specific purpose not to get offspring in the long term to a lifetime. The purpose of this study was to analyze the factors that influence women of childbearing age in choosing contraceptives. The type of research used is analytic study with case control study design. The number of samples in this study were 32 cases and 960 control groups. The results obtained from Sidomulyo village that there is influence of knowledge, perception, attitudes of women of childbearing age and health workers in the use of tubectomy contraception methods in Sidomulyo village.